Implementasi Program Imtaq dan Tahsin Qur’an di SMA Negeri 1 Rambutan Kabupaten Banyuasin - Firzal, Juanda; Karolina, Asri; Afriantoni, Afriantoni; Yuniar, Yuniar (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe the implementation of the Imtaq and Tahsin Qur’an Programs at SMA Negeri 1 Rambutan. The study employs a qualitative method with a field study approach. Data were collected through in-depth interviews with Islamic Education teachers, homeroom teachers, tahsin instructors, and students; observations of religious activities and tahsin learning; as well as documentation such as activity schedules, implementation reports, and program evaluation archives. Data analysis techniques include data collection, data presentation, verification, and conclusion drawing. The results of the study show that the Imtaq program is implemented through well-planned religious habituation activities such as morning prayers, tadarus, salat duha, salat zuhur in congregation, and Islamic studies aimed at fostering spiritual discipline and noble character. Meanwhile, the Tahsin Qur’an program is carried out through gradual coaching based on students’ ability levels, using the talaqqi and sima’an methods, along with periodic evaluations that have proven effective in improving students’ Qur’anic reading quality. The implementation of both programs is supported by effective supervision systems and strong collaboration among the school, teachers, students, and parents, ensuring the programs run effectively and sustainably